Pengaruh Perubahan Ritme Sirkadian terhadap Marker Inflamasi pada Pedagang Pasar Subuh di Kota Palangka Raya - Rinny Ardina; Dwi Purbayanti (Jurnal Surya Medika (JSM), 2020)
Dawn market traders in Pasar Seram Palangka Raya City with sleep deprivation and alteration of sleep pattern has the potential risk of circadian rhythm disruption. Circadian rhythm disruption is the beginning of various chronic diseases such as coronary heart disease. One of the inflammation markers that can be used to assess the onset of atherosclerosis and coronary heart disease is the platelet profile (platelet count, mean platelet volume (MPV), platelet distribution width (PDW) and plateletcrit (PCT)). This study aimed to describe the effect of circadian rhythm disruption of inflammation marker as a platelet profile in dawn market traders in Pasar Seram Palangka Raya City. The descriptive observational method with a cross-sectional design was used in this study. Samples obtained as many as 100 people using purposive sampling technique. The examination of the platelet profile was done by an automated method using a hematology analyzer. The results showed, there was 6% with high platelet count and it only in women. Whereas for platelet indices in men, there was 6% with high MPV, 74% with high PCT, and 10% with low PCT. In women, there was 84% with high PCT and 6% with low PCT (6%). The result showed there were inflammation and accumulation of platelets as a result of circadian rhythm disruption in dawn market traders.